SCIENTIFIC MAPPING OF THE GLOBAL TREND IN FINANCIAL LITERACY AND BEHAVIOR - Riza Rizqiyah (Bajang Institute, 2025)
Exploring the financial literacy trend has been interesting topic, it has the crucial ro;e as the fundamental knowledge and skill for individuals in this modern economy. Wheter the individuals are employed in salaried jobs or are self employed entrepreneurs, undersatnding financial pronciples is critical to managing income, investments, and future planning. This study aims to investigate how the evolution of the financial literacy just happened, like the structure the thematic development from scholarly research on financial literacy and also financial behaviour. Employed the bibliometric methods using the biblioshiny tools as the application within the bibliometrix R-package. The data were sourced from the scopus database and spanned publication between 2020 until mid-2025 and found 1574 articles and journals. The research followed has three majorstages: data collection, organize and evolution This study found that there is the increase interest in financial literacy and behaviour, with a notable surge in publication from 2023 onwards.